Implementasi Model Problem Based Learning Dipadu LKPD Berbasis STEM untuk Meningkatkan Keterampilan Berpikir Kritis pada Materi Pencemaran Lingkungan - Zainatul Hasanah; Andi Ulfa Tenri Pada*; Safrida Safrida; Wiwit Artika; Mudatsir Mudatsir (Jurnal Pendidikan Sains Indonesia, 2021)
The learning process only focuses on the material by memorizing concepts, students do not use LKPD to do practical work optimally, so the biology learning process in schools does not encourage students to practice critical thinking skills. This study aims to improve students' critical thinking skills by using the PBL learning model combined with STEM-based worksheets on environmental pollution conceptin class 10th SMA Negeri Bireuen district. The approach used is experimental design, the method used is quasi-experimental, with a pretest-posttest design non-equivalent control group design. Population in class 10th IPA SMAN 1 and SMAN 2 Peusangan designed 252 people. The sampling technique used was purposive sampling technique. The research sample was 140 students. The number of samples in the experimental class was 71 people and 69 people in the control class. The instrument used was a reasoned multiple choice question accompanied by a rubric. The data analysis used was n-gain and independent t-test. The results showed that the critical thinking skills obtained was 0.93, with an increase in class critical thinking skills including the high category. The results of the independent sample t-test obtained Sig. (0,000) α (0.05) then Ha is accepted, so it is suggested that there are differences in the critical thinking skills of students between the experimental class and the control class on environmental pollution material in class X SMAN Bireuen. The implementation of PBL learning model combined with STEM-based LKPD can improve students' critical thinking skills on environmental pollution material in class 10th SMA Negeri Bireuen Regency.